Inter- and intra-rater reliability of modified near-infrared camera to assess superficial lymphatic system in breast cancer-related lymphedema - Brahma, Bayu; Yusuf, Prasandhya Astagiri; Priambodo, Purnomo Sidi; Harimurti, Kuntjoro; Haryono, Samuel Johny; Harlim; Suryadi; Paskahenru, Mahesa; Lesmana, Rika; Manangka, Rumuat Semuel Wullul; Taher, Akmal; Panigoro, Sonar Soni (Faculty of Medicine Universitas Indonesia, 2026)
BACKGROUND Near-infrared (NIR) fluorescence imaging is one of the most useful diagnostic methods for breast cancer-related lymphedema (BCRL). It utilizes indocyanine green (ICG) lymphography, which requires a commercial camera that is not widely available. This study aimed to qualitatively assess the reliability of the modified NIR camera in diagnosing BCRL. METHODS This prospective cross-sectional study was conducted between December 2023 and December 2024 in breast cancer (BC) patients with BCRL. A commercial mirrorless digital camera was modified by incorporating an excitation light source and spectral filters to enable NIR imaging. To evaluate the camera reliability, intra- and inter-observer agreements were assessed using Kappa analysis. Three independent observers evaluated dermal backflow patterns of lymphatic flow: linear, splash, stardust, and diffuse patterns. RESULTS 60 BC patients with BCRL resulting in 280 images were included. The mean (standard deviation) age was 54.7 (10.1) years and body mass index were 27.1 (4.5) kg/m². Most patients had stage IIA BC (40%) and stage IV ICG lymphography (38%). Intra-observer analysis showed observers 1 and 2 of had a Kappa of 1.00 (95% confidence interval [CI]: 1.00–1.00), while observer 3 had Kappa of 0.99 (95% CI: 0.97–1.00). Inter-observer analysis between observers 1 and 2 showed Kappa 1.00 (95% CI: 1.00–1.00), while observers 1–3 and 2–3 had Kappa of 0.99 (95% CI: 0.97–1.00). Observer 3 misinterpreted 3 linear as splash patterns. CONCLUSIONS This study showed a high inter- and intra-observer agreements making it reliable for BCRL diagnosis.